ADOLESCENT PERIOD CHANGES POST COVID-19 INFECTION AND VACCINATION : CROSS SECTIONAL STUDY - Riska Hakim; Mia Dwi Agustiani; Gunarmi; Siti Maimunah (Jurnal Smart Kebidanan, 2025)
Background: Covid-19 infection has been followed by several post-impacts. As well as vaccination, can also provide some effects, named Adverse Event After Immunization. Objective:Thisresearch aims to investigate to analyseperiode changes in adolescent who have been infected covid-19 infection and vaccinations. Method: This is a cross-sectional survey-based reseach, the number sample is  271 adolescent in Yogyakarta who have been infected with Covid-19 to fill-out the study questionnaire. Results: The study was consist of adolescent, age 13-17 years old. Results showed that 52,7% post-covid infection (n = 143), 94 (65,7%) have a change in the amount of days between two periods, as well as from a change in the amount of blood loss. And then 66,8% post-vaccination (n = 181), 113 (62,4%)have a change in the amount of days between two periods, as well as from a change in the amount of blood loss. Conclusions: This Study revealed that Covid-19 infection and vaccination could be effect the adolescent period. Further prospective research should be done to evaluate how long the irregularities period